(untitled) (Research, Society and Development, 2020)
The objective of the research was to identify the profile of childbirth care in a usual risk maternity hospital in the centre of the Brazilian state of Rio Grande do Sul. This is a cross-sectional study that investigated the labour’s duration, the use of technologies, the type of delivery and interventions. Data are from a patient record book in the approximate period of 7 months of the year 2017, composing a total of 485 birth deliveries analyzed from IBM SPSS version 23 software. A cross-table was made, applying the Qui-square test and identifying the statistically significant differences, with results with value p<0,05. The results indicate that there is an association between the type of delivery and the use of medical interventions during labour (p<0,001). In the delivery types cesarean section (PC) and vaginal birth with episiotomy (PNE), the percentages come close to 90% with the use of medical interventions. As for normal delivery (PN) and normal delivery with laceration (PNL), these percentages reduce to less than 50%. It is concluded that the deliveries type PNL and PN are accompanied, most of the times, by obstetric nurses, and that minimizes the use of interventions. The deliveries type PNE and PC are attended by physicians, who maintain more interventive approaches. These data are important for the professionals’ reflection and allow to outline strategies to qualify the assistance.